A Time-Series Analysis of the Scale of Coercive Journal Self-Citation and its Effect on Impact Factors and Journal Rankings. Issue 2 (15th March 2019) - Humphrey, Christopher; Kiseleva, Oxana; Schleicher, Thomas
ABSTRACT: The growing institutional significance of impact factors and journal rankings currently stands alongside serious concerns about the scale and distorting effects of the practice of coercive journal self-citation. Survey-based studies have highlighted journals suspected of such coercion but there has been very little empirical analysis of actual citation practice and the respective impact on journal quality rankings. This paper collects information on actual self-citation trends over the period 2000–2012 for all business and management journals indexed in Journal Citation Reports and finds evidence of sudden and sharp increases in self-citation relative to outside citation. This paper also finds that two leading hybrid journal ranking systems, the UK's 2010 Association of Business Schools (ABS) and the 2013 Australian Business Deans Council (ABDC) rankings, do not discriminate between legitimate and coercive self-citation. Collectively, these findings have implications regarding the institutional reliance placed on citation counts as quantitative measures of accountability. However, the deterrent potential of our analysis, especially given the ease with which coercive self-citation behavior can be empirically detected from publicly available data, could provide an important limit on the spread of performativity.